2020
DOI: 10.1080/01902148.2020.1742252
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of pleural and perilesional subcutaneous microdialysis to assess porcine experimental pulmonary contusion

Abstract: Background: Severe thoracic trauma affects 55% of patients with multiple traumatic injuries and may lead to acute lung injury or acute respiratory distress syndrome. Pulmonary trauma differs clinically and biologically from lung injury of other origins and carries a mortality rate of 10%. Treatment options are limited, and it is not possible to monitor the progression of lung injury with specific biomarkers. Microdialysis of pleural fluid may offer a viable entry to monitor the lung directly and specifically. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…For animals randomized to BABT, a focally severe pulmonary contusion was induced, as previously described 8,9 by a gunshot perpendicular to a body armor panel fixed on the mid-lateral right thorax with two 3-cm wide girdles. The armor protection consisted of a 300 Â 255 mm ceramic ballistic plate (weight 3 Kg) and 14 additional 0.24 mm aramid layers placed behind the plate (Åkers Krutbruk Protection Inc.) (Figure 2).…”
Section: Babtmentioning
confidence: 99%
See 2 more Smart Citations
“…For animals randomized to BABT, a focally severe pulmonary contusion was induced, as previously described 8,9 by a gunshot perpendicular to a body armor panel fixed on the mid-lateral right thorax with two 3-cm wide girdles. The armor protection consisted of a 300 Â 255 mm ceramic ballistic plate (weight 3 Kg) and 14 additional 0.24 mm aramid layers placed behind the plate (Åkers Krutbruk Protection Inc.) (Figure 2).…”
Section: Babtmentioning
confidence: 99%
“…3,[6][7][8] We have described an immediate and severe hypoxia following high velocity projectile BABT in swine. 9 The mechanisms are not sufficiently elucidated. Hypoxia may result from hypoventilation, low inspired air O 2 (PIO 2 ), diffusion limitation, low ventilation-perfusion (V 0 A/Q 0 ) regions or shunt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,5 BABT is well described in gelatin models but the correlation with human physiology is low. 3,[6][7][8] We have shown that high velocity projectile BABT in swine results in an immediate and severe hypoxia, 9 which is attributed to a severe and transient decrease in ventilation perfusion mismatch (V' A/Q') to <1 and increased venous admixture (Q's/Q't) in the exposed lung. 10 BABT injury mechanisms are complex and differ from other types of thoracic trauma, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The BABT-simulator was validated to inflict similar back-face signature and impression velocity, when fired directly at the naked chest as a high velocity projectile assault rifle 7.62 mm bullet impacting a ceramic plate armor placed on the thorax at 800 m/s. [8][9][10] Using the BABT-simulator, we investigated the relationship between impact parameters (E k ) and immediate and potentially life-threatening pulmonary consequences. Quantitative estimates of the effect of oxygenation and venous admixture (Q's/Q't) on gas exchange was measured in relation to the E k absorbed by the thorax.…”
Section: Introductionmentioning
confidence: 99%